THE COVERAGE OF PERIPHERAL CULTURAL MANIFESTATIONS IN BRAZILIAN JOURNALISM: A CASE STUDY OF CULT MAGAZINE - Norberto Ribeiro Soares, Filipe; Cerqueira Cunha, Cintia (Revista Gênero e Interdisciplinaridade, 2023)
This article intends to analyze the 183rd edition - of September 2013 - of the cultural magazine of national circulation called Cult. Passing through discussions about precepts exposed by the cultural industry and forms of coverage carried out by cultural journalism, the objective is to analyze how manifestations considered peripheral are represented in Brazilian journalism, especially in Cult magazine. Although the journal alludes to rap, carioca funk and tecnobrega, the study will bring a historical, political and social detail only on the first one because it is the style with the greatest representation on the magazine’s cover and also to centralize the analysis in search of better results.